Acute lung injury and repair : scientific fundamentals and methods - Altemeier, William A. 1910-1983; Chow, Yu-Hua; D'Alessio, Franco R.; Feghali-Bostwick, Carol; Felton, Lindsey M.; Schnapp, Lynn M. (Cham, Switzerland : Humana Press, 2017)
Acute Respiratory Distress Syndrome (ARDS) remains an important cause of morbidity and mortality worldwide, and the incidence is predicted to increase with the aging population Several clinical disorders can initiate ARDS, including pneumonia, sepsis, gastric aspiration and trauma but despite intense research over the past 40 years, we still have an incomplete understanding of the pathophysiology of the disease and treatment remains largely supportive. This book provides an overview of acute lung injury and repair, describes current animal models to study lung injury and reviews current methodologies to study and measure lung injury and repair. Special emphasis is given to state of the art techniques and methods and relevance to human disease. Acute Lung Injury and Repair: Scientific Fundamentals and Methods is a useful resource for physicians and scientists who are interested in experimental model systems for insight into ARDS pathogenesis and treatment strategies. ​
La función de los autores fue determinada por el catalogador
Keywords: PULMONES -- HERIDAS, LESIONES, ETC; PULMONES -- HERIDAS, LESIONES, ETC. -- TRATAMIENTO; PULMONES -- ENFERMEDADES -- FISIOPATOLOGÍA; MEDICINA REGENERATIVA